Fostering Students’ Capacity to Reflect Through Formative Assessment Strategies (2019)
ABSTRACT: This action-research aimed at fostering students’ capacity to reflect on their learning process through Formative Assessment Strategies (FAS). It was conducted in a public school in Rionegro-Antioquia with 33-eighth graders during approximately one year. Action strategies included two stages. The first one involved familiarization of students with FAS such as self and peer assessment, rubrics and feedback by means of guiding questions, discussions and formats. The second stage put into practice FAS seeking to promote students’ reflection on their own learning process. Data gathering instruments included teacher’s journal, focus group, and students’ artefacts. Findings revealed that students’ capacity to reflect allowed them to take actions to benefit their learning process and support students’ reflection towards task development and assessment. Some implications for this project included: (a) intentionally conducting activities to familiarize students with the FAS and (b) time investment at the beginning of the process while students get familiarized with the strategies.